Kajian pembuatan snack bar Tepung pisang (musa sapientum) dan kacang merah (phaseolus vulgaris l.) Sebagai alternatif selingan rendah indeks glikemik bagi penderita diabetes melitus tipe II - Nugroho, Arie; Amir, Aswita; Sunarto, Sunarto; Tamrin, Abdullah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Diabetes mellitus (DM) is one of the most common chronic diseases faced by people around the world. In patients with diabetes mellitus, blood glycose levels increase due to a deficiency of the hormone insulin. Blood sugar levels can be controlled by food intake. In this study, a processed product was made in the form of a snack bar that is suitable for consumption by people with DM as one of the choices of snack food. The snack bar is made from banana flour which has a high fiber content, and red beans which have a low glycemic index (GI) value. The purpose of this study was to determine the characteristics of banana and red bean flour snack bars with natural sweeteners for patients with type II diabetes mellitus.This study used an experimental method with one repetition. Observations consisted of four formulations of banana flour: red bean ratio including F1 (100.0), F2 (90:10), F3 (80:20), (70:30). The parameters studied in this study were orgonoleptic test using hedonic test (color, aroma, taste, and overall acceptance of the product). The snack bar made from banana flour and red beans that is most preferred with the highest overall acceptance likert scale value is F4, which has a ratio of 70% banana flour and 30% red beans The price of the snack bar per portion weighing 30 grams is Rp 4,500 It contains 187 kcal of energy, 596 grams of protein, 485 grams of fat, 3163 grams of carbohydrates, and 314 grams of fiber. In further research, it is necessary to conduct a proximate test to determine the nutritional content of snack bars made from banana flour and red beans specifically. And to increase fiber content in snack bar products can be done by adding ingredients that are rich in fiber, such as oatmeal, nuts, and seeds.